2018
DOI: 10.1111/jdi.12844
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of insulin resistance in non‐obese Asian Indian and Chinese men

Abstract: Aims/IntroductionIndian individuals are more insulin resistant (IR) than Chinese individuals, even among those with a non‐obese body mass index (BMI). However, BMI often underestimates body fat in Indian individuals, and it remains unclear whether Indians would remain more IR than Chinese individuals when both BMI and body fat are equally matched.Materials and MethodsUsing the hyperinsulinemic‐euglycemic clamp with stable‐isotope infusion, we comprehensively assessed IR between 13 non‐obese Indian men with 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Consistent with our study, other authors also reported higher insulin resistance in ethnic Indians than Chinese or Malays8–13 21 25 and Europeans,9 22 23 26 28 31 even after adjustments for BMI or waist circumference 21–23. In a study conducted in Singapore where body fat and insulin sensitivity were directly measured, Indians were also more insulin resistant than Chinese, independent of adiposity 24.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our study, other authors also reported higher insulin resistance in ethnic Indians than Chinese or Malays8–13 21 25 and Europeans,9 22 23 26 28 31 even after adjustments for BMI or waist circumference 21–23. In a study conducted in Singapore where body fat and insulin sensitivity were directly measured, Indians were also more insulin resistant than Chinese, independent of adiposity 24.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted in Singapore where body fat and insulin sensitivity were directly measured, Indians were also more insulin resistant than Chinese, independent of adiposity 24. However, this was not observed in two other studies conducted in Canada and Singapore when matched for body fat 9 11. In a study that examined the skeletal muscle transcriptome in Chinese, Malays, and Indians, the expression of SNRK and AMPKα2 genes involved in glucose uptake was lowest in Indians 25.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is reasonable to postulate that these traditional risk factors may at least partly contribute to the accelerated diabetes progression in Malays with T2DM. Although several studies have examined ethnic differences in insulin resistance among the 3 ethnic groups in Singapore, 20,21 studies comparing beta cell function across ethnic groups are relatively scarce. One early study showed that healthy and lean Malay males exhibited a lower insulin secretory capacity that was accompanied by a higher glucose excursion in response to mixed-meal tolerance test as compared to their Chinese and Indian counterparts.…”
Section: Discussionmentioning
confidence: 99%